B1 siRNA Increases de novo DNA Methylation of B1 Elements and Promotes Wound Healing in Diabetic Rats - Yasom, Sakawdaurn; Khumsri, Wilunplus; Boonsongserm, Papatson; Kitkumthorn, Nakarin; Ruangvejvorachai, Preecha; Sooksamran, Apasee; Wanotayan, Rujira; Mutirangura, Apiwat (Frontiers in Cell and Developmental Biology, 2022)
Alu (B1 in rodents) hypomethylation, commonly found in diabetes mellitus patients, increases DNA damage and, consequently, delays the healing process. Alu siRNA increases Alu methylation, reduces DNA damage, and promotes cell proliferation. Aim: To explore whether B1 siRNA treatment restores B1 hypomethylation, resulting in a reduction in DNA damage and acceleration of the healing process in diabetic rat wounds. Methods: We generated splinted-excisional wounds in a streptozotocin (STZ)-induced type I diabetic rat model and treated the wounds with B1 siRNA/Ca-P nanoparticles to generate de novo DNA methylation in B1 intersperse elements. After treatment, we investigated B1 methylation levels, wound closure rate, wound histopathological structure, and DNA damage markers in diabetic wounds compared to nondiabetic wounds. Results: We reported that STZ-induced diabetic rat wounds exhibited B1 hypomethylation, wound repair defects, anatomical feature defects, and greater DNA damage compared to normal rats. We also determined that B1 siRNA treatment by Ca-P nanoparticle delivery restored a decrease in B1 methylation levels, remedied delayed wound healing, and improved the histological appearance of the wounds by reducing DNA damage. Conclusion: B1 hypomethylation is inducible in an STZ-induced type I diabetes rat model. Restoration of B1 hypomethylation using B1 siRNA leads to increased genome stability and improved wound repair in diabetes. Thus, B1 siRNA intervention may be a promising strategy for reprogramming DNA methylation to treat or prevent DNA damage-related diseases.